An Analysis of Representative Acts and Language Functions Represented on Code Mixing and Code Switching Used by Yuvi Phan in Her Instagram Reels - Krismalika Cinta Della Hermaya; Winantu Kurnianingtyas Sri Agung (CV. Rustam, 2023)
The research aims to analyze the types of representative acts and the types of language functions represented in code-mixing and code-switching that appear in Yuvi Phan's Instagram reels. This research was conducted in library research. So, qualitative research was used. The researcher utilized a transcript of Yuvi Phan Instagram reels as the data in this research. Data was gathered through documentation. After that, the data were analyzed through content analysis. The results presented that there were 25 data that were categorized into three types of representative acts represented on code switching and code mixing that were found in Yuvi Phan's Instragram reels. There were 14 data of assertions, 9 data of suggestions, and 2 data of statements. The second result presented that 25 data were categorized into three types of language functions of representative act represented on code switching and code mixing that were found in Yuvi Phan's Instragram reels. They were giving information, persuading people, and sharing opinions. There were 16 data on giving information, eight on persuading people, and one on sharing opinions. So, based on the explanation above, the researcher concluded that representative acts and language functions can coexist in utterances, as well as in code switch and code mix, and that representative acts and language functions can coexist in representative acts marked by words or phrases. Moreover, representative acts and language functions in Yuvi Phan's Instagram reels can be the reference as a media for the instructing educational experience.